Geneva convention, commentary : for the amelioration of the condition of the wounded and sick in armed forces in the field - the geneva conventions of 12 august 1949 - Siordet, Frederic; Pictet, Jean S. ([S.l.] : International Committee of the Red Cross, 1995)
466 pages.
Box set.